2010
DOI: 10.1016/j.bmc.2010.05.039
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of a triazine dendrimer that sequesters iron(III) using 12 desferrioxamine B groups

Abstract: The synthesis of a third generation triazine dendrimer, 1, containing multiple, iron-sequestering desferrioxamine B (DFO) groups is described. Benzoylation of the hydroxamic acid groups of DFO and formation of a reactive dichlorotriazine provide the intermediate for reaction with the second generation dendrimer displaying twelve amines. This strategy further generalizes the “functional monomer” approach to generate biologically active triazine dendrimers. Dendrimer 1 is prepared in seven steps in 35% overall y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Using the G2 dendrimer available at the kilogram scale, Mr. Jongdoo Lim and Mr. Vince Venditto installed the iron chelator desferrioxamine B (in protected form, Chart 7 ) as a dichlorotriazine and reacted with 12 primary amines presented on the dendrimer periphery [ 37 ]. The poly(monochlorotriazine) that resulted was ‘capped’ with 4-hydroxylmethylpiperidine, leading to a construct that was 56 wt% drug.…”
Section: Resultsmentioning
confidence: 99%
“…Using the G2 dendrimer available at the kilogram scale, Mr. Jongdoo Lim and Mr. Vince Venditto installed the iron chelator desferrioxamine B (in protected form, Chart 7 ) as a dichlorotriazine and reacted with 12 primary amines presented on the dendrimer periphery [ 37 ]. The poly(monochlorotriazine) that resulted was ‘capped’ with 4-hydroxylmethylpiperidine, leading to a construct that was 56 wt% drug.…”
Section: Resultsmentioning
confidence: 99%
“…Dendrimers are highly defined hierarchical structures, much more regular than structurally somehow-related hyperbranched polymers, with the hydrodynamic radius usually below the renal threshold and therefore with renal elimination as the primary way of elimination. Iron-chelating dendrimers were synthesized [102,115] with deferoxamine iron-chelating moieties. Nanogels are gel-structured nanoparticles and with appropriate iron-chelating moieties [116][117][118][119]; however, due to their larger size, they must be biodegradable to allow elimination.…”
Section: Polymers and Nanospecies With Bound Chelators To Be Applied Parenterallymentioning
confidence: 99%
“…Later studies revealed that polymeric sequestrants based on the hydroxypyridinone hexadentate (CP254) provide the optimum coordination interactions with iron (III) to form highly stable complexes [72,73]. Similar approaches using polymers modified with various iron-chelating motifs were reported and shown in vivo iron-binding capability in rats when given orally [74,75]. This strategy has also been extended to other metals such as aluminum, cadmium, and lead [54,7678].…”
Section: Polymeric Sequestrantsmentioning
confidence: 99%